2021
DOI: 10.3103/s1060992x21030085
|View full text |Cite
|
Sign up to set email alerts
|

Neural Networks and Forecasting COVID-19

Abstract: For analysis tasks, time counts are of interest – values recorded at some, usually equidistant, points in time. The calculation can be performed at various intervals: after a minute, an hour, a day, a week, a month, or a year, depending on how much detail the process should be analyzed. In time series analysis problems, we deal with discrete-time, when each observation of a parameter forms a time frame. The same can be said about the behavior of Covid-19 over time. In this paper, we solve the problem of predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The potential of deep neural networks has been explored by numerous studies involving different areas related to the COVID-19 pandemic, such as for virus detection [ 10 12 ], classification of image exams such as X-Ray and computed tomography (CT) [ 13 , 14 ], and time-series forecasting [ 15 17 ]. Considering the use of artificial intelligence on different battlefronts against the COVID-19 pandemic, El-Rashidy et al [ 18 ] conducted a survey of the most important applications and found 5 types: diagnosis, transmission estimation, study of the characteristics of different populations and the effects of Covid-19, vaccine development and the study of other drugs, supporting applications.…”
Section: Related Workmentioning
confidence: 99%
“…The potential of deep neural networks has been explored by numerous studies involving different areas related to the COVID-19 pandemic, such as for virus detection [ 10 12 ], classification of image exams such as X-Ray and computed tomography (CT) [ 13 , 14 ], and time-series forecasting [ 15 17 ]. Considering the use of artificial intelligence on different battlefronts against the COVID-19 pandemic, El-Rashidy et al [ 18 ] conducted a survey of the most important applications and found 5 types: diagnosis, transmission estimation, study of the characteristics of different populations and the effects of Covid-19, vaccine development and the study of other drugs, supporting applications.…”
Section: Related Workmentioning
confidence: 99%
“…where, β 2 -similar β 1 the hyperparameter that controls the exponential decay rates of the sliding, and is taken as 0.999 as the most appropriate value for machine learning problems [39,40]. However, these slides are initialized as vectors close to zero (and the values will accumulate for a long time).…”
Section: Determination Of the Dataset And Neural Network Architecturesmentioning
confidence: 99%